the legitimacy Provisions in Human Organ Transplantation (Islamic Sciences Journal, 2023)
ABSTRACT                   The issue of human organ transplantation is one of the contemporary topics that has become in our days one of the possible applications, and it went out of what used to be called hypothetical issues that the jurists assumed and tried to find their  Provisions.    Another aspect of the importance of this issue is the need of people in certain cases to transplant these organs, so is it permissible to take an organ from a place in the human body and implant it elsewhere? Or is it permissible to transplant it into another body? Or did he take it from a clean animal or an impure animal and plant it in a person? What is the  Provisions  on taking this organ from a dead person?then I state some of the obtained results follows:1-It is permissible to transfer organs from one  place to another when there is a need.2 - It is permissible to transfer the organs of what may be eaten to the human body when there is a need.3 - It is permissible to use unclean organs from animals, on conditions, that they are needed and there is no substitute for them4-The permissibility of using human organs on conditions: First: there is a need for them. Second: there are no pure organs,. Third: The absence of of unclean animals to take their place and that they are obtained legally.
Keywords: Provisions ,legitimacy, Transplant, organs , human.